Mineralogy of the MSL Curiosity landing site in Gale crater as observed by MRO/CRISM. Issue 14 (23rd July 2014) - Seelos, Kimberly D.; Seelos, Frank P.; Viviano‐Beck, Christina E.; Murchie, Scott L.; Arvidson, Raymond E.; Ehlmann, Bethany L.; Fraeman, Abigail A.
Abstract Orbital data acquired by the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) and High Resolution Imaging Science Experiment instruments on the Mars Reconnaissance Orbiter (MRO) provide a synoptic view of compositional stratigraphy on the floor of Gale crater surrounding the area where the Mars Science Laboratory (MSL) Curiosity landed. Fractured, light‐toned material exhibits a 2.2 µm absorption consistent with enrichment in hydroxylated silica. This material may be distal sediment from the Peace Vallis fan, with cement and fracture fill containing the silica. This unit is overlain by more basaltic material, which has 1 µm and 2 µm absorptions due to pyroxene that are typical of Martian basaltic materials. Both materials are partially obscured by aeolian dust and basaltic sand. Dunes to the southeast exhibit differences in mafic mineral signatures, with barchan dunes enhanced in olivine relative to pyroxene‐containing longitudinal dunes. This compositional difference may be related to aeolian grain sorting.